A soproni hospesek jogállása és helye a határőrzési feladatokat ellátó nyugat-magyarországi hospesközösségek között a 13. században - Borsodi-Nagy , Barnabás (Díké - A Márkus Dezső Összehasonlító Jogtörténeti Kutatócsoport folyóirata, 2026)
In Hungary the 13th century was the era of the privileging of the hospes communities. Some of these communities – mostly in the western part of the country – also performed border guard duties. By comparing their letters of privileges with those of the other hospes communities, we can see some significant correlations especially in connection with duty-free trade and fairs.